61.4k views
0 votes
? Given that
a = 1, b = 3 and c = 2
work out
62 - 2ac

User Soywod
by
5.4k points

2 Answers

2 votes

Answer:

Step-by-step explanation: Substitute the values in the given expression
62 - 2ac as follows -


62 - 2ac= 62-2(1)(2)

Here,
a=1 and
c=2


62 - 2ac= 62-4\\62 - 2ac= 58

Hence, the value of
62 - 2ac is
58.

User Manolo Santos
by
5.2k points
4 votes

Explanation:

Given that a = 1, b = 3 and c = 2 solve for: 62 - 2ac

62 - 2ac

62 - 2(1)(2)

62 - 4

= 58

User Buggieboy
by
5.6k points